Evaluation of skin natural change function in split-thickness skin graft - Helen Limarda; Tamia Asri Jeser; Johanes Andrew; Rokhim Suryadi; Teddy Tjahyanto (Institute of Computer Science (IOCS), 2022)
Treatment for severe burns has improved rapidly in the last 20 years. Nowadays, patients can survive with burns covering up to approximately 90% of the body, although they often face permanent physical impairment. This type of research is a literature review. A literature review was conducted to gather information regarding the evaluation of skin natural change function in the split-thickness skin graft. This research is a type of review article that aims to obtain information about acne based on bio-markers. Source of data used secondary sources. The method of data collection through collecting data was from research articles taken within the last five years. Skin grafting remains an essential step on the reconstructive surgeon ladder. Meanwhile, the basic premise has remained similar results over the years. New techniques and devices have contributed to significantly improved functional and aesthetic results. Advances in the production of skin substitutes have provided better options to treat patients and will continue to be an essential and dynamic component of this field in the future.